Inclusive methodologies for carrying out complex scientific-industrial research - Giuseppe Mincolelli; Michele Marchi (Techne, 2021)
Contemporary society is changing by reason of technical, technological and social processes that are evolving faster than ever before. Thinking and designing with a Human Centered Design (HCD) approach means expanding the catchment area of the possible users of our product or service without losing specificity and relevance in terms of performance. It is necessary to conceive spaces, services and products that are able to adapt to the variable characteristics of the context, and which can dynamically respond to needs that vary in time for the same user base. The HC project assumes that an organized multidisciplinary approach has to be applied to identify a suitable, effective and articulated response for this scenario. The paper investigates application tools that can be useful to pursue the objectives of complex interdisciplinary projects. Some national and international researches carried out by the project team, supporting and using a HCD methodology will be specifically described.